Amyloid β-Exposed Human Astrocytes Overproduce Phospho-Tau and Overrelease It within Exosomes, Effects Suppressed by Calcilytic NPS 2143—Further Implications for Alzheimer's Therapy - Chiarini, Anna; Armato, Ubaldo; Gardenal, Emanuela; Gui, Li; Dal Prà, Ilaria (Frontiers in Neuroscience, 2017)
The two main drivers of Alzheimer’s disease (AD), amyloid-β (Aβ) and hyperphosphorylated Tau (p-Tau) oligomers cooperatively accelerate AD progression, but a hot debate is still ongoing about which of the two appears first. Here we present preliminary evidence showing that Tau and p-Tau are expressed by untransformed cortical adult human astrocytes in culture and that exposure to such cells to an Aβ42 proxy, Aβ25-35, which binds the calcium-sensing receptor (CaSR) and activates its signaling, significantly increases intracellular p-Tau levels, an effect CaSR antagonist (calcilytic) NPS 2143 wholly hinders. The astrocytes also release both Tau and p-Tau by means of exosomes into the extracellular medium, an activity that could mediate p-Tau diffusion within the brain. Preliminary data also indicate that exosomal levels of p-Tau increase after Aβ25-35 exposure, but remain unchanged in cells pre-treated for 30-min with NPS 2143 before adding Aβ25-35. Thus our previous and present findings raise the unifying prospect that AβCaSR signaling plays a crucial role in AD development and progression by simultaneously activating (i) the amyloidogenic processing of amyloid precursor holoprotein, whose upshot is a surplus production and secretion of Aβ42 oligomers, and (ii) the GSK-3β-mediated increased production of p-Tau oligomers which are next released extracellularly inside exosomes. Therefore, as calcilytics suppress both effects on Aβ42 and p-Tau metabolic handling, these highly selective antagonists of pathological AβCaSR signaling would effectively halt AD’s progressive spread preserving patients’ cognition and life quality.